2011
DOI: 10.1021/pr100729z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pre-Diagnosis Biomarkers of Immune Activation and Inflammation: Insights on the Etiology of Lymphoma

Abstract: The DNA-modifying processes that are involved in B lymphocyte activation, somatic hypermutation (SHM) and IgH class switch recombination (CSR), have the potential to lead to genetic errors that lead to the genesis of B cell cancers, such as lymphoma. Given the potential contribution of these immune mechanisms to the development of cancer, assessment of the expression of cytokines and other immune stimulatory molecules that drive B cell activation, prior to lymphoma diagnosis, may provide insights into the etio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 54 publications
4
43
0
2
Order By: Relevance
“…The observation that circulating high levels of IL-6, and IL-10 were repeatedly detected prior to AIDS-NHL diagnosis implies a role of these cytokines in driving B-cell stimulation in the development of lymphoma. 36,37 Overall, these findings indicate that HIV-1 viremia, circulating microbial products and pro-inflammatory cytokines all play Funding: This study was supported in part by grants from the Italian Ministry of Health program "Alleanza Contro il Cancro (ACC-4)", "Program Integrato Oncologia (RO 4/2007)", and Associazione Italiana per la Ricerca sul Cancro.…”
Section: Discussionmentioning
confidence: 98%
“…The observation that circulating high levels of IL-6, and IL-10 were repeatedly detected prior to AIDS-NHL diagnosis implies a role of these cytokines in driving B-cell stimulation in the development of lymphoma. 36,37 Overall, these findings indicate that HIV-1 viremia, circulating microbial products and pro-inflammatory cytokines all play Funding: This study was supported in part by grants from the Italian Ministry of Health program "Alleanza Contro il Cancro (ACC-4)", "Program Integrato Oncologia (RO 4/2007)", and Associazione Italiana per la Ricerca sul Cancro.…”
Section: Discussionmentioning
confidence: 98%
“…There exists strong evidence that tumor growth can be actively controlled by the host immune system and ILs are known to play a significant role in immune response regulation (Vendrame and Martínez-Maza, 2011). Previous studies have shown that; polymorphisms in a gene encoding an inflammatory mediator affect the biological activity of the corresponding protein, and may be associated with oncogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of non-Hodgkin's lymphoma (NHL) remains unclear, subclinical immune dysfunction is the most consistently identified risk factor, and dysregulation of cytokines may mediate its progression (Vendrame and Martínez-Maza, 2011). A variety of NHL subtypes are recognized, but cases are generally classified into two major groups: B-and T-cell lymphomas.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the B-cell activation is associated with DNA-modifying processes, including Ig class switch recombination (CSR) in Ig heavy chain genes (IgH) and somatic hypermutation (SHM) (Vendrame and Martinez-Maza 2011). Moreover, higher levels of cytidine deaminase, a DNA-mutating enzyme that plays a role in both IgH CSR and SHM, have been found to be related to AIDS-NHL development (Epeldegui et al 2007).…”
Section: Lymphoma Blood Biomarkers Among Hiv Patientsmentioning
confidence: 99%